1995
DOI: 10.2175/106143095x131411
|View full text |Cite
|
Sign up to set email alerts
|

Composition and variability of leachate from recent and aged areas within a municipal landfill

Abstract: A leachate study was conducted at a large, operating, regional municipal solid waste (MSW) landfill near Seattle, Washington, to examine differences in composition and emission rates between old and new areas of the fill. The landfill began operation in 1966, was receiving approximately 2000 tpd of MSW and had 30 × 106 m3 (∼12 × 106 tonnes) waste in place at the time of this study. The two areas studied had average ages of 3.7 and 16 years, and contained 5.7 × 106 and 2.04 × 106 tonnes of MSW, respectively. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 2 publications
1
10
0
2
Order By: Relevance
“…This suggested that the total amount of organic material in the landfill was decreasing with increasing age. The decrease of COD and TOC over time was consistent with several literatures, although Ragle et al (1995) reported increase in COD and TOC with age. However, according to Reinhart and Grosh (1998) there was no significant trend observed for COD and BOD of leachates.…”
Section: Leaching Of Organicssupporting
confidence: 92%
“…This suggested that the total amount of organic material in the landfill was decreasing with increasing age. The decrease of COD and TOC over time was consistent with several literatures, although Ragle et al (1995) reported increase in COD and TOC with age. However, according to Reinhart and Grosh (1998) there was no significant trend observed for COD and BOD of leachates.…”
Section: Leaching Of Organicssupporting
confidence: 92%
“…This permanent contact with landfill leachate leads to a significant water pollution (Ragle et al, 1995;Howard et al, 1996;Jensen et al, 1999;Baun et al, 2000;Khattabi et al, 2002). Here, wastes have been land filled since 1983 that include domestic, industrial and hospital refuse with no preliminary treatment (JICA, 1997;Tazi, 2001).…”
Section: Site Characteristicsmentioning
confidence: 99%
“…Research has shown that the composition of land®ll leachate from the same source, as well as from different sources, is extremely variable (Chian and DeWalle, 1976;Bolton and Evans, 1991), and suggests that leachate quality can change as a land®ll ages (Chian and DeWalle, 1976). The leachate composition of recent and older areas within a municipal land®ll has been studied and it has been con®rmed that it alters with time (Ragle et al, 1995).…”
Section: Background Informationmentioning
confidence: 99%